Acute megakaryoblastic transformation from essential thrombocythemia - Tariq M. Roshan; Ashish B. Rajput; Philip Berardi; Ruth Padmore (Elsevier, 2017)
Essential thrombocythemia (ET) is a Philadelphia chromosome-negative myeloproliferative neoplasm characterized by sustained thrombocytosis. Its transformation into acute leukemia is a rare event (5% at 20 years). Transformation can be spontaneous or related to therapy. Acute leukemias most often associated with transformation from ET are myeloblastic or myelomonoblastic leukemias. There are very few case reports of ET transforming into acute megakaryoblastic leukemia. Here we report a case of transformation to acute megakaryoblastic leukemia in an elderly female patient who was treated with hydroxyurea for ten years. After 10-years with stable disease she presented and rapidly deteriorated with acute megakaryoblastic leukemia with high JAK2V617F mutant allele burden and high p53 expression. This case provides another example of the poor outcome of acute megakaryoblastic transformation of essential thrombocythemia. Keywords: Essential thrombocythemia, Acute megakaryoblastic leukemia, Transformation